The case for dosing dabigatran: how tailoring dose to patient renal function, weight and age could improve the benefit-risk ratio - Safouris, Apostolos; Triantafyllou, Nikos; Parissis, John; Tsivgoulis, Georgios (Therapeutic advances in neurological disorders, 2015)
Dabigatran is increasingly being used in clinical practice for the thromboprophylaxis in atrial fibrillation as a convenient therapy that needs no drug level monitoring. However, analysis of the data of the same clinical trial that led to the adoption of dabigatran in fixed-dosing regimens has indicated a small subgroup of patients that could be either over-treated, risking bleeding, or under-treated, risking embolism. Additional post-marketing data lends support to the favorable therapeutic profile of dabigatran but at the same time raises doubts about patient characteristics such as weight, age, renal function and their pharmacokinetic effects that, in some cases, could be serious enough to expose a minority of patients to risk. We will present a clinical case of a patient with an ischemic stroke while on dabigatran that was found with low dabigatran plasma levels and we will discuss the currently available data on the effects of inherent patient characteristics on dabigatran pharmacokinetics, the clinical impact of dabigatran plasma levels on safety and efficacy as well as the possibility of improving the risk-benefit profile of this agent by tailoring the dose for selected patient groups.
Keywords: atrial fibrillation; dabigatran; dosing